KALINGA STYLE ART AND ARCHITECTURE OF SOME VAISHNAVITE TEMPLES OF PRACHI VALLEY OF ODISHA IN EASTERN INDIA - Mohapatra, Ratnakar; Majhi, Baikuntha (International Journal of Psychosocial Rehabilitation, 2020)
The art and architecture of the Vaishnavite temples of the Prachi Valley are important parts of the temple building activities and techniques of the whole of Odisha in eastern India. Most of the earlier art historians and senior scholars had traced the artistic activities and techniques of notable temples of the Prachi Valley, like the Madhavananda Temple, Lakshmi-Narayana Temple, Lakshmi-Narasimha Temple, etc., but they have not covered the minor Vaishnavite temples of the said valley. All the extant temples of the Prachi Valley, including the present Vaishnavite temples, belong to the Kalinga style of temple architecture of Odisha. In fact, the minor Vaishnavite temples of the Prachi Valley are the sacred shrines of the coastal belt of Odisha, considering their religious significance. The artistic features and religious aspect of the extant minor Vaishnavite temples of the Prachi Valley attract scholars, art historians, and archaeologists to undertake research works. Some of the Vaishnavite temples of the Prachi Valley that have to be discussed here are 1. Madhavananda Temple at Adaspur , 2. Narasimhanatha Temple at Paribasudeipur, 3. Gopinatha Temple at Varahipur, 4. Madhavananda Temple at Pahanga, 5. Lakshmi-Kanta Temple at Nuagaon, and 6. Madhavananda Temple at Balara. Methodologically, both the primary and secondary sources have been used in this article to trace the artistic designs and architectural features along with the religious significance of the above Vaishnavite temples of the Prachi Valley of Odisha in Eastern India.